First‐principles modeling of molecular crystals: structures and stabilities, temperature and pressure. (19th December 2016) - Hoja, Johannes; Reilly, Anthony M.; Tkatchenko, Alexandre
Abstract : The understanding of the structure, stability, and response properties of molecular crystals at finite temperature and pressure is crucial for the field of crystal engineering and their application. For a long time, the field of crystal‐structure prediction and modeling of molecular crystals has been dominated by classical mechanistic force‐field methods. However, due to increasing computational power and the development of more sophisticated quantum‐mechanical approximations, first‐principles approaches based on density functional theory can now be applied to practically relevant molecular crystals. The broad transferability of first‐principles methods is especially imperative for polymorphic molecular crystals. This review highlights the current status of modeling molecular crystals from first principles. We give an overview of current state‐of‐the‐art approaches and discuss in detail the main challenges and necessary approximations. So far, the main focus in this field has been on calculating stabilities and structures without considering thermal contributions. We discuss techniques that allow one to include thermal effects at a first‐principles level in the harmonic or quasi‐harmonic approximation, and that are already applicable to realistic systems, or will be in the near future. Furthermore, this review also discusses how to calculate vibrational and elastic properties. Finally, we present a perspective on future uses of first‐principles calculations for modeling molecular crystals and summarize the many remaining challenges in this field. WIREs Comput Mol Sci 2017, 7:e1294. doi: 10.1002/wcms.1294 This article is categorized under: Structure and Mechanism > Computational Materials Science Electronic Structure Theory > Ab Initio Electronic Structure Methods Electronic Structure Theory > Density Functional Theory Abstract : First‐principles methods can nowadays not only be used to accurately model structures and stabilities of molecular crystals, but also to calculate vibrational‐ and elastic properties, thermal expansion coefficients, and heat capacities, as shown in the figure.